Complementary detection of macroalgal diversity through visual surveys and eDNA metabarcoding in Lombok’s intertidal zone, Indonesia - NURLIAH BUHARI; EDWIN JEFRI; AYU ADHITA DAMAYANTI; PARYONO PARYONO; NENIK KHOLILAH; MAYA LAKSHMI GANAPATHY (Society for Indonesian Biodiversity, 2025)
Abstract. Buhari N, Jefri E, Damayanti AA, Paryono, Kholilah N, Ganapathy ML. 2025. Complementary detection of macroalgal diversity through visual surveys and eDNA metabarcoding in Lombok’s intertidal zone, Indonesia. Biodiversitas 26: 5638-5646. Macroalgae are fundamental architects of tropical marine ecosystems, yet their diversity in the Indonesian archipelago, a global marine?biodiversity hotspot, remains poorly documented. This study aimed to assess macroalgal diversity in the intertidal zones around Lombok Island, Indonesia, by comparing data from morphological surveys and eDNA metabarcoding. Visual sampling was carried out along five 100 m transects, each divided into 1?×?1?m quadrats, yielding 24 species dominated by green and brown algae; red algae were observed at only a few stations. In parallel, seawater from each station was pooled, filtered, and the 18S rRNA region amplified and sequenced, uncovering an additional 21 red?algal taxa that were absent from the morphological inventory; only Palisada?sp. was detected by both methods. Visual surveys provided detailed morphological and ecological information, whereas eDNA revealed cryptic, microscopic, and morphologically indistinct taxa. The contrasting outputs reflect methodological biases and highlight the benefits of integrating traditional and molecular approaches. These findings provide the first comprehensive baseline of macroalgal diversity in Lombok and emphasize the value of combining field and eDNA surveys for long-term monitoring and conservation of coastal ecosystems, a scalable model applicable to other understudied reef systems throughout the Indo?Pacific.